Serum cystatin C is closely associated with euthyroid Hashimoto's thyroiditis in adult female Chinese patients. Issue 8 (August 2020) - Qin, Qiaojing; Yang, Min; Ke, Wencai; Zhao, Jinying; Ding, Heyuan
Objective: The aim of our study was to explore the association between serum cystatin C (CysC) and euthyroid Hashimoto's thyroiditis. Methods: There were 119 female euthyroid Hashimoto's thyroiditis patients and 225 healthy controls who were recruited. Serum CysC, thyroid function, thyroid autoantibodies, fasting glucose, liver enzymes, and lipid profile were determined. Clinical parameters were compared between two groups. Results: Serum CysC levels were significantly higher in euthyroid Hashimoto's thyroiditis patients compared with controls. In the lowest, middle, and highest tertile groups of CysC, the percentage of Hashimoto's thyroiditis was 15.9%, 34.2%, and 53.5%, respectively. The percentage of Hashimoto's thyroiditis was significantly higher in the highest tertile than in the lowest and middle tertiles. Spearman's correlation analysis showed that serum CysC levels were negatively correlated with free triiodothyronine (FT3 ), and positively correlated with serum thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TGAb). Logistic regression analysis showed that serum CysC was independently related to the status of euthyroid Hashimoto's thyroiditis. Conclusions: The present study shows the first evidence suggesting that serum CysC levels are positively correlated with TPOAb and TGAb. Serum CysC might underlie the pathophysiologic features of euthyroid Hashimoto's thyroiditis.